2006
DOI: 10.1590/s0100-29452006000200010
|View full text |Cite
|
Sign up to set email alerts
|

Ingestão de seiva do xilema de laranjeiras 'Pêra' e 'Valência' (Citrus sinensis (L.) Osbeck) sadias e infectadas por Xylella fastidiosa, pelas cigarrinhas vetoras Oncometopia facialis e Dilobopterus costalimai (Hemiptera: Cicadellidae)

Abstract: Estudou-se o efeito da infecção pela bactéria Xylella fastidiosa, agente causal da Clorose Variegada dos Citros (CVC), sobre a taxa de ingestão de seiva do xilema de plantas cítricas por duas espécies de cigarrinhas vetoras (Hemiptera: Cicadellidae). Foram utilizados pés-francos de laranjeira-doce (Citrus sinensis) das variedades 'Pêra' e 'Valência', infectadas por X. fastidiosa da linhagem 9a5c, por meio de inoculação mecânica. Os insetos utilizados nos experimentos foram coletados em campo, sendo um represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Because B. xanthophis spends more time ingesting xylem sap on infected plants still asymptomatic than on plants with CVC symptoms, our work supports a previous hypothesis (Marucci et al 2005, Montesino et al 2006) that asymptomatic infected plants may be more important sources of inoculum than symptomatic ones. A higher acquisition efficiency oíX.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Because B. xanthophis spends more time ingesting xylem sap on infected plants still asymptomatic than on plants with CVC symptoms, our work supports a previous hypothesis (Marucci et al 2005, Montesino et al 2006) that asymptomatic infected plants may be more important sources of inoculum than symptomatic ones. A higher acquisition efficiency oíX.…”
Section: Discussionsupporting
confidence: 87%
“…This could explain why B. xanthophis spent significantly less time ingesting from the xylem of symptomatic than asymptomatic citrus plants. It may also explain the results of Montesino et al (2006), who observed lower honeydew excretion rates when the sharpshooters O. fadalis and D. costalimai were confined on citrus plants with severe CVC symptoms than on healthy ones. However, chemical or nutritional differences in the xylem sap between diseased and healthy plants may exist, and could also infiuence xylem ingestion by sharpshooters.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations